John Foster Dulles : piety, pragmatism, and power in U.S. foreign policy - Immerman, Richard H. (Biographies in American foreign policy., 2014)
John Foster Dulles was one of the most influential and controversial figures in the history of twentieth-century U.S. foreign relations. Active in the field for decades, Dulles reflected and was a reflection of the tension that pervaded U.S. international conduct from its evolution as a global power in the early twentieth century through its emergence as the 'leader of the Free World' during the Cold War. His life and career embody the best and most troubling aspects of American foreign policy as it progressed toward international supremacy while swaying between altruism and self-interest.